Classification of South Sulawesi Rice Quality Based on Website Using Machine Learning - Salmiah; Basalamah, Abdullah; Altim, Muhammad Zainal; Kasman; Kasim, Fadly (Program Studi Pendidikan Teknologi Infromasi UMK, 2026)
Rice is a staple food commodity in Asian countries like Indonesia, but there are still challenges in quality assurance and standardization. The objectives of this research are to design and to develop a website-based system to classify the quality of rice using machine learning methods, to analyze the performance of the website-based South Sulawesi rice quality classification system, and to determine the accuracy of the classification system. This research uses the Convolutional Neural Network (CNN) method to classify rice quality based on some characteristics such as texture, shape, color, and size. The research succeeded in designing and developing a website-based system called